Study impedance and temperature behavior of LFP battery as function of relative humidity and temperature under various conditions - Keyoonwong, Wiwat; Phiphuannok, Kankawi; Janesawatpong, Kittipot; Seeboonrueang, Kotchapon; Amnuaysap, Nuttapum; Puttawong, Titichaya (My University, 2024)
Nowadays, lithium-ion batteries are widely employed in a lot of applications. For example, using batteries to provide energy for Electric Vehicles. In use, Batteries are charged and discharged in many cycles, which impacts battery aging. Battery aging causes capacity reduction and internal resistance increase. As is well known, the battery resistance changes with temperature and state of charge (SOC). However, no one has yet studied whether relative humidity affects the battery resistance or not. In this paper, behavior of LFP batteries as function of relative humidity and temperature under various conditions is analyzed. During the aging process, a battery impedance meter was performed at various conditions to analyze the change of the battery impedance due to relative humidity and temperatures. Additionally, the time required to charge the battery under different conditions was analyzed.
Keywords: Impedance; LFP; Li-ion Battery; Relative humidity; State of Charge; Temperature